Do perceived social support mitigate the influence of infertility stigma on fertility quality of life? - Al Sabbah, Saher; Tantry, Ansarullah; Bayliss-Pratt, Lisa (Frontiers in Global Women's Health, 2025)
IntroductionInfertility is a medical condition that affects both males and females and can cause the individuals biopsychosocial, spiritual, and medical detriments. Quality of life among such couples or singles is a matter of concern. The question that we need to address is whether infertility affects the quality of life. Does the stigma associated with Infertility deter Infertile females from leading normal lives? This research explores how infertility stigma affects the quality of life of infertile females and whether perceived social support reduces the stress related to stigma thereby contributing to a better quality of life among females battling Infertility in India.MethodsParticipants from Jammu and Kashmir who identified as currently or previously infertile discussed their feelings about fertility stigma, the quality of their fertility-related social support, and their fertility quality of life. Only 302 fully complete questionnaires were obtained from the 351 identified individuals who were given data collection tools. Structural Equation Modeling (SEM) was used to treat data.ResultsIt was seen that infertility stigma and perceived social support had an impact on fertility quality of life, either directly or indirectly. Infertility quality of life was reduced by stigma (β = -.413, SE = .017, p ≤ .01 level of significance, CI, 95%), and this link was partially mediated by infertile female's perceptions of social support (β = .512, p ≤ .01 level of significance, CI, 95%). In other words, it can be said that the negative effects of infertility stigma were buffered by perceived social support and improved fertility quality of life. Additionally, the sense of stigma was adversely linked with the overall quality of past fertility-related support.DiscussionThe findings of study confirms that perceived social support significantly mitigates the negative impact of infertility-related stigma on fertility quality of life among infertile females, highlighting the crucial role of emotional and social resources in mitigating distress. These findings emphasize the importance of encouraging supportive environment and interventions to enhance quality of life in females experiencing infertility stigma.